New hosts and localities for species of Cancricepon Giard & Bonnier, 1887 Isopoda: Epicaridea: Bopyridae) with description of two new species and comments on the relationship between Cancricepon and Trapezicepon Bonnier, 1900 - An, Jianmei; Wang, Mingxiao; Boyko, Christopher B.; Williams, Jason D. (Zootaxa, 2019)
The genus Cancricepon Giard & Bonnier, 1887 is recorded for the first time from Australia, the Maldives, Papua New Guinea and Taiwan. Four species of Cancricepon are reported here, and two are new to science. Cancricepon choprae (Nierstrasz & Brender à Brandis, 1925) is reported from the Gulf of Mexico on the Florida coast, infesting a new host, Micropanope cf. sculptipes Stimpson, 1871. Cancricepon castroi n. sp. is described from Australia, the Maldives, Japan and Papua New Guinea parasitizing coral crabs of the family Trapeziidae. Cancricepon cf. multituberosum An, Yu & Williams, 2012 is recorded from a specimen of Leptodius affinis (De Haan, 1835) from Taiwan. Specimens previously misidentified as C. choprae parasitizing Scalopidia spinosipes Stimpson, 1858, from China are described as C. beibusinus n. sp. All known hosts and localities of species of Cancricepon are summarized, and a key to the species in the genus is provided. The similarities between species of Cancricepon and the type species of Trapezicepon Bonnier, 1900, are discussed and Trapezicepon thalamitae Markham, 1985, is transferred to Scyracepon Tattersall, 1905.